Bezprawny dowód z korespondencji internetowej stron w postępowaniu cywilnym - Gadek, Błażej (Wydawnictwo C.H. Beck, 2018)
The aim of the present study is the analysis of admissibility of introducing illegally obtained evidence from the Internet correspondence into civil proceedings. In the absence of an appropriate legal norm in the Civil Procedure Rules (CPR), which would directly define the (in)admissibility of the relevant phenomenon, it becomes necessary to make legal comparative studies of constitutional regulations, as well as refer to acts of international law. At the same time, the author reviews tendencies appearing in literature and judicial decisions within the scope of possibility of using the above-mentioned illegal evidence in civil proceedings.
Keywords: illegal evidence; unlawful evidence; Internet correspondence; civil trial; fruit of the poisonous tree doctrine